Identification of Pests and Diseases in Long Bean Plants (Vigna sinesis L.) in Ploso Village, Jumapolo, Karanganyar - Antik Murwani; Riska Satya Graha Putrimulya; Hania Nurbayti; Qurota A'yun; Nur Rokhimah Hanik (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
Long bean (Vigna sinesis L.) is a horticultural plant that is easy to cultivate. Cultivation of long bean plants certainly has several factors that can reduce production yields such as environmental factors, pest attacks, and diseases. This study aims to determine the pests and diseases that generally attack long bean plants and the symptoms they cause. This study used direct observation method (Systematic sampling) to determine the percentage of pest and disease attacks on long bean plants. From the total number of plants in the location, 5 plant samples were taken to be observed. Based on the pest and disease identification research that has been carried out, it was found that some of the symptoms that arise due to pest/disease attacks on most of the long bean plants were found. Symptoms that appear include damage to flower buds and leaves with holes caused by black ladybugs (Brachyplatys sp.); leaf curl, leaves and stems turn black due to aphids (Aphis craccivora); jagged leaf edges, and holes caused by grasshoppers (Oxya sp.) and lasiocampidae caterpillars; thickening of the leaf veins on young leaves, leaves shrinking caused by Bean Common Mosaic Virus (BCMV); The leaves turn yellow and the bone blanching occurs due to the Mungbean Yellow Mosaic Virus (MYMV).